The impact of a feed-in tariff on wind power development in Germany - Claudia Hitaj; Michael Schymura; Andreas Löschel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
We estimate the impact of a feed-in tariff for renewable power on wind power investment in Germany at the county level from 1996-2010 controlling for windiness and access to the electricity transmission grid. After the Renewable Energy Law (EEG) was passed in 2000, the feed-in tariff became linked to wind power potential, such that more windy locations received a lower incentive per unit of output. We find that a 1 e-cent/kWh increase in the feed-in tariff rate would increase additions to capacity at the national level by 764MWper year from 1996- 2010 or 1,528 MW per year from 2005-2010. We analyze counterfactual scenarios, in which a uniform incentive is offered instead of the wind-dependent EEG incentive. Significantly more wind power plants are installed along the northern coastal counties in the uniform incentive scenario. We find that while the uniform incentive results in greater total wind power output per installed capacity, the EEG is ultimately more efficient by achieving 1% greater wind power output per euro and 3.7% greater reductions in power sector emissions per euro. In addition, we find a significant response from investors to an EEG provision that shifted the cost of transmission system upgrades from wind power developers to grid operators in 2000. The lack of a signal on scarcity of transmission capacity has likely resulted in a distribution of wind power plants that makes suboptimal use of existing infrastructure, necessitating investment in new transmission corridors.
Keywords: Q0; Q42; Q50; 330; wind power; feed-in tariff; electricity transmission